Inter-firm linkages, business strategies and performance of micro and small enterprises: a case study of micro and small industrial clusters in the province of Central Java, Indonesia - Hoetoro, Arif (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2011)
This study investigates the interplay of inter-firm linkages and business strategies and their impacts on performance of micro and small enterprises (MSEs) that operate in small industrial clusters in the Province of Central Java, Indonesia. Many studies in this field were commonly conducted in partial works whilst a substantial work that discussed a more comprehensive picture on their development by means of focusing on causal nexus of inter-firm linkages, business strategies and performances of MSEs which were constructed in an integrated model has not been explored in detail. As an attempt to fill the gap, this study intends to examine twofold namely (1) the relational dimensions of inter-firm linkage mechanism and business strategies on performance of MSEs and (2) the pathways in which MSEs have benefited the linkages and business strategies to attain their goals. To do so, this study carries out an empirical assessment of the causal nexus connecting inter-firm linkages and business strategies to performances of 310 MSEs that operate in 14 small industrial clusters in Central Java. Given such triangular relationships, this study found that inter-firm linkages seem to be less effective in affecting MSEs' performances rather than business strategies. Based on qualitative data collected from the field survey, it is found that the lack of trust among the clustered entrepreneurs and the existence of institutional problems caused the ineffectiveness of inter-firm linkages to positively contribute to MSEs' performances. As a result, while MSEs in the clusters cooperate with each other as a consequence of proximity advantage of clusters, they also hinge on their own business strategies in order to attain better performance of the firms.